2021
DOI: 10.1021/acs.iecr.1c01304
|View full text |Cite
|
Sign up to set email alerts
|

Selective Iron Catalysts for Direct Fischer–Tropsch Synthesis to Light Olefins

Abstract: Ethylene, propylene, and butylene may be directly produced through selective CO hydrogenation over Fischer–Tropsch to light olefins (FTO) catalysts. It is known that Fe-based catalysts promoted by S/Na synergistic effect may reach a C2 =–C4 = hydrocarbon selectivity of 53% at 20 bar. Herein, we report a zeolite-free, potassium-promoted iron FTO catalyst modulated by high-temperature annealed composite oxides, 15%Fe/2%K2O/83%ZnAl8O13, exhibiting a C2 =–C4 = hydrocarbon selectivity of 64.4% at a total pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The highest C2-C4 olefin selectivity of 52.1% was obtained over the N1 catalyst at 340 °C and CO conversion of 38.3%, and hydrogenation of olefins to paraffins was successfully suppressed, while the content of olefins in the fractions of C2, C3, and C4 hydrocarbons reached ultra-high values of 90.7%, 94.7%, and 92.9%, respectively [98]. In another study by Liu et al [100], the 15%Fe/2%K2O/83%ZnAl2O4•3Al2O3 catalyst exhibited the high C2-C4 olefin selectivity of 64.4% at 360 °C 20 bar, and CO conversion of 15.2%. The content of olefins in C2, C3, and C4 fractions were 88%, 92%, and 89%, respectively.…”
Section: Alumina Supported Catalystsmentioning
confidence: 87%
“…The highest C2-C4 olefin selectivity of 52.1% was obtained over the N1 catalyst at 340 °C and CO conversion of 38.3%, and hydrogenation of olefins to paraffins was successfully suppressed, while the content of olefins in the fractions of C2, C3, and C4 hydrocarbons reached ultra-high values of 90.7%, 94.7%, and 92.9%, respectively [98]. In another study by Liu et al [100], the 15%Fe/2%K2O/83%ZnAl2O4•3Al2O3 catalyst exhibited the high C2-C4 olefin selectivity of 64.4% at 360 °C 20 bar, and CO conversion of 15.2%. The content of olefins in C2, C3, and C4 fractions were 88%, 92%, and 89%, respectively.…”
Section: Alumina Supported Catalystsmentioning
confidence: 87%
“…In addition, the metal valence state as well as the redox properties and interface structures of PTOs can be adjusted by elemental doping, or by partial substitution of the A and/or B sites, to provide controlled selectivity for the target products [128]. According to previous studies, perovskite-type catalysts have shown high catalytic activity in FTS [129][130][131] and RWGS reactions [132,133]. Therefore, as a potential material, Fe-doped perovskite catalysts have also been investigated for CO 2 hydrogenation to hydrocarbons.…”
Section: Perovskite-type Oxidesmentioning
confidence: 99%
“…It is immeasurable to estimate the astounding prosperity crude oil has offered to society with the provision of hydrocarbon fuels (gasoline, diesel fuel, and jet fuel), oxygenates (dimethyl ether, methanol, and higher alcohols), and other chemical building blocks (aromatics and light olefins). However, growing concerns following crude oil depletion and environmental concerns about their exploitation have sparked the search for alternative carbon sources and processes that are sustainable and environmentally benign. Accordingly, syngas (a mixture of CO and H 2 ), which can be produced from carbon­(IV) oxide, biomass, coal, natural gas, and carbon-based waste has become a sustainable option to supply these chemical feedstocks, oxygenates, and fuels, traditionally produced from crude oil. Syngas conversion is a catalytic process with extensive studies allocated to efficient catalyst development for the selective production of valued products. Catalysts required for the successful synthesis of the valued chemicals and fuels normally include a metallic species in the form of single atoms, clusters, carbides, oxides, or alloy particles (e.g., Co, Rh-, AuPd-, metallic Fe, Fe 5 C 2 -based catalysts). , However, these metallic species are challenged with poor catalytic stability with a hydrocarbon product distribution that barely differs from the prediction of the Anderson-Schultz-Flory (ASF) probability model; thus, the production of desired products remains a difficult challenge. Overcoming product selectivity limitations with further improvements using composite materials for tandem catalysis via strategic designs have become important areas of research.…”
Section: Introductionmentioning
confidence: 99%